Water-absorbent resin for fixative and its use

A polyacrylic acid (salt)-based water-absorbent resin with a controlled displacement rate is developed to address handling issues after absorption, achieving improved cohesion and preventing scattering and dust generation in industrial applications.

JP7665475B2Active Publication Date: 2025-04-21NIPPON SHOKUBAI CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021144931
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-03
Filing Date
2021-09-06
Publication Date
2025-04-21
Estimated Expiration
2041-09-06

AI Technical Summary

Technical Problem

Existing water-absorbent resins used as fixatives for industrial applications, such as water-containing roses and litter materials, face challenges in handling after absorption, particularly in preventing scattering and dust generation during transport, due to inadequate physical properties.

Method used

A polyacrylic acid (salt)-based water-absorbent resin with a displacement rate of 60% or less after swelling for 20 hours, which is below a predetermined value, is developed. This resin exhibits excellent handling after absorption, allowing it to bind with solid matter and prevent scattering and dust generation.

Benefits of technology

The water-absorbent resin demonstrates improved handling and cohesion after absorption, effectively preventing scattering and dust generation during transport, making it suitable for use as a fixative in industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665475000001
    Figure 0007665475000001
Patent Text Reader

Abstract

To provide a water-absorbing resin for a fixative that is excellent in handleability after liquid absorption in a solid-liquid coexistence.SOLUTION: Provided is a water-absorbing resin for a fixative having a filtration rate of 60% or less after being swollen with pure water for 20 hours.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a water-absorbent resin for use as a fixing agent. [Background technology]

[0002] Water-absorbent resins are resins that are water-swellable and water-insoluble, and have excellent water-absorbency properties. As a result, they are widely known for their use (hygienic applications) as constituent materials (water absorbents) in hygienic materials such as disposable diapers, sanitary napkins, and incontinence pads.

[0003] On the other hand, water-absorbent resins are also used (industrial applications) as fixatives for wet bulk matter, livestock manure treatment materials (bedding materials), waste liquid solidification, etc. Patent Documents 1 to 3 disclose techniques for using water-absorbent resins for industrial applications. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6825738 [Patent Document 2] International Publication WO2014 / 103005 [Patent Document 3] Japanese Patent Application Publication No. 62-44126 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the conventional techniques as described in Patent Documents 1 to 3, the physical properties of the water absorbent resin suitable for industrial applications (particularly, for use as a fixing agent) have not been fully examined, and there is room for improvement in terms of prevention of scattering and dust from a belt conveyer or the like, particularly when the amount of water absorption is small.

[0006] In the above-mentioned circumstances, one aspect of the present invention aims to provide a water-absorbent resin for a fixing agent, which has excellent handleability after absorbing liquid in the presence of both solid and liquid, and use of the same. [Means for solving the problem]

[0007] The present inventors have found that when a water absorbent resin is added to pure water and stirred for 10 minutes, the stirring is stopped, the resin is left to stand for 20 hours, and then stirred at 500 rpm for a further 10 minutes, and the filtration rate after swelling in pure water for 20 hours, which is the proportion of the filtrate when the pure water is filtered, is equal to or less than a predetermined value, the water absorbent resin has excellent handleability after absorbing liquid when used as a fixative for hydrated loose material (water-absorbed loose material), bedding material, and the like, and have completed the present invention.

[0008] That is, one embodiment of the present invention is as follows. [1] A water-absorbing resin for use as a fixative, which is a polyacrylic acid (salt)-based water-absorbing resin and has a filtration rate of 60% or less after swelling in pure water for 20 hours. [2] The water-absorbent resin for a fixing agent according to [1], which has a filtration rate of 45% or less after swelling in pure water for 20 hours. [3] The water-absorbent resin for a fixing agent according to [1] or [2], which has a filtration rate of 70% or less after swelling in pure water for 10 minutes. [4] The water-absorbent resin for a fixing agent according to any one of [1] to [3], which has a filtration rate of 50% or less after swelling in pure water for 10 minutes. [5] The water-absorbent resin for a fixing agent according to any one of [1] to [4], having a CRC of 35 g / g or more. [6] The water-absorbent resin for a fixing agent according to any one of [1] to [5], having a CRC of 38 g / g or more. [7] The water-absorbent resin for a fixing agent according to any one of [1] to [6], having a mass median particle diameter (D50) of 200 to 800 μm. [8] A fixing agent comprising the water-absorbing resin for fixing agents according to any one of [1] to [7]. [9] The fixative according to [8], which is a fixative for moist bulk material.

[10] A method for modifying moist rose product, comprising a step of contacting the fixing agent according to [8] or [9] with the moist rose product.

[11] A method for producing a modified hydrated rose product, comprising a step of contacting the fixative according to [8] or [9] with hydrated rose product.

[12] The fixative according to [8], which is a fixative for bedding materials. Effect of the Invention

[0009] According to the water-absorbent resin of one embodiment of the present invention, it is possible to provide a water-absorbent resin for a fixing agent, which has excellent handleability after absorbing liquid in the presence of both solid and liquid, and a technology for using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each configuration described below, and various modifications are possible within the scope of the claims, and embodiments and examples obtained by appropriately combining the technical means disclosed in different embodiments and examples are also included in the technical scope of the present invention. In addition, all academic literature and patent documents described in this specification are incorporated herein by reference. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more and B or less."

[0011] 1. Technical Concept of the Present Invention In the case of using a water absorbent resin for industrial purposes, that is, as a fixing agent for materials in which solid and liquid coexist, such as wet loose matter and bedding materials, the conventional techniques had problems with the handleability of the water absorbent resin after absorbing liquid, in particular, with respect to prevention of scattering and generation of dust during transportation, etc.

[0012] In the above-mentioned circumstances, the present inventors have conducted extensive research to provide a water-absorbent resin for industrial use that is excellent in handleability after absorbing liquid. As a result, they have newly found that a water-absorbent resin having a filtration rate after swelling in pure water for 20 hours lower than a predetermined value is excellent in handleability after absorbing liquid, and have completed the present invention.

[0013] The water-absorbent resin according to one embodiment of the present invention (hereinafter referred to as the present water-absorbent resin) has a filtration rate after swelling in pure water for 20 hours that is lower than a predetermined value, so that it is easy to become sticky when absorbing liquid and easy to be consolidated after absorbing liquid. In other words, the present water-absorbent resin can bind and fix solid matter (e.g., powder, etc.) remaining after absorbing liquid in solid-liquid coexistence. Therefore, scattering and dust generation can be prevented, and handling is improved, so that it is extremely useful as a fixing agent for water-containing loose matter, bedding material, waste liquid solidification, etc. For this reason, the present water-absorbent resin can also be said to be a water-absorbent resin for fixing agents.

[0014] Although the technology of using water-absorbent resins for industrial applications has been publicly known, the physical properties of water-absorbent resins suitable for industrial applications have hardly been studied. In particular, the technology of using a water-absorbent resin having a filtration rate after swelling in pure water for 20 hours lower than a predetermined value as a fixing agent has not been disclosed so far, and it can be said to be a surprising new finding.

[0015] 2. Definitions of Terms [2-1. Water-absorbing resin] In this specification, the term "water-absorbent resin" refers to a water-swellable, water-insoluble crosslinked polymer, which is generally particulate. In addition, "water-swellable" means that the absorbency under no load (CRC) as defined in NWSP 241.0.R2(15) is 5 g / g or more, and "water-insoluble" means that the extractable content (Ext) as defined in NWSP 270.0.R2(15) is 50 mass% or less.

[0016] The water-absorbing resin can be appropriately designed according to its application, and is not particularly limited, but is preferably a hydrophilic cross-linked polymer obtained by cross-linking an unsaturated monomer having a carboxyl group. In addition, it is not limited to a form in which the total amount (100 mass%) is a polymer, and may be a surface-cross-linked one or a composition containing additives, etc., within a range in which the above-mentioned performance is maintained.

[0017] [2-2.NWSP] "NWSP" stands for "Non-Woven Standard Procedures-Edition 2015," which was jointly issued by EDANA (European Disposales And Nonwovens Associations) and INDA (Association of the Nonwoven Fabrics Industry) to standardize evaluation methods for nonwoven fabrics and their products in the United States and Europe, and indicates standard measurement methods for water-absorbent resins. Unless otherwise specified, in the present invention, the physical properties of the water-absorbent resin are measured in accordance with "NWSP."

[0018] [3. Water-absorbing resin] The water-absorbing resin is a polyacrylic acid (salt)-based water-absorbing resin, and has a filtration rate of 60% or less after swelling in pure water for 20 hours. Since the water-absorbing resin has the above-mentioned composition, it is excellent in handleability after absorbing liquid in the presence of solid and liquid, and therefore can be particularly suitably used as a fixing agent. Therefore, it can be said that the water-absorbing resin is a water-absorbing resin for fixing agents.

[0019] The water absorbent resin is not particularly limited as long as it is a polyacrylic acid (salt)-based water absorbent resin that has a filtration rate of 60% or less after swelling in pure water for 20 hours and satisfies the definition described in (2-1) above. In this specification, the term "poly(meth)acrylic acid (salt) water absorbent resin" refers to a polymer containing (meth)acrylic acid (salt) as a main component.

[0020] In addition, in this specification, "acid (salt)" means "acid and / or its salt", and "(meth)acrylic" means "acrylic and / or methacrylic". That is, "poly(meth)acrylic acid (salt)-based water absorbent resin" means a water absorbent resin mainly composed of (meth)acrylic acid (salt) as a repeating unit. Here, "mainly composed of (meth)acrylic acid (salt)" specifically means that, of the total monomers (excluding crosslinking agents) used in polymerization, (meth)acrylic acid (salt) is preferably contained in an amount of 50 to 100 mol%, more preferably 70 to 100 mol%, further preferably 90 to 100 mol%, and particularly preferably substantially 100 mol%.

[0021] The present water-absorbing resin may be a water-absorbing resin mainly composed of (meth)acrylic acid (salt), and may contain a repeating unit (other repeating unit) other than (meth)acrylic acid (salt). As the other repeating unit, for example, an unsaturated monomer having a carboxyl group other than (meth)acrylic acid (salt) can be suitably used.

[0022] [Physical properties of water-absorbent resin] <Filtration rate after swelling in pure water for 20 hours> As a water-absorbent resin having excellent handling properties after absorbing liquid, it is preferable that the gel strength of the water-absorbent resin after absorbing liquid is relatively weak, the soluble content is relatively high, and the particle size (physical factors such as contact area) of the water-absorbent resin after absorbing liquid is relatively fine. It is considered that these complex factors affect the handling properties after absorbing liquid. However, it is difficult to individually determine the extent to which the above-mentioned various factors affect the handling properties of the water-absorbent resin after absorbing liquid, and therefore it is difficult to define a water-absorbent resin having excellent handling properties after absorbing liquid by the above-mentioned conventional factors (parameters). In such a situation, the present inventor has found that a water-absorbent resin having excellent handling properties after absorbing liquid can be suitably selected by the filtration rate (%) after swelling with pure water, which is a new physical property value that can include all the effects of these factors.

[0023] The water absorbent resin has a filtration rate (%) of 60% or less after swelling in pure water for 20 hours, preferably 45% or less, more preferably 35% or less, and particularly preferably 30% or less. If the filtration rate after swelling in pure water for 20 hours is 60% or less, the water absorbent resin after absorbing liquid is likely to be sticky when absorbing liquid and is likely to be collected after absorbing liquid, and is excellent in handleability after absorbing liquid. In this specification, the "filtration rate after swelling in pure water for 20 hours" may be referred to as the "20-hour filtration rate".

[0024] The filtration rate of the water-absorbent resin after swelling in pure water for 20 hours was measured as follows. 600 g of pure water is weighed out and placed in a plastic container with a diameter of 80 mm and a height of 210 mm (volume of 1 L), and a cylindrical stirrer with a length of 40 mm and a thickness of 8 mm is placed in the container and stirred at 500 rpm. 0.3 g of water-absorbing resin is placed in the container (in the weighed pure water) and stirred at 500 rpm for 10 minutes. Then, stirring is stopped and the mixture is left to stand for 20 hours. After standing, the mixture is stirred at 500 rpm for another 10 minutes. The stirred liquid is evenly placed in three funnels (inverted cone-shaped main body inlet diameter φ140 mm, main body height 120 mm, foot diameter 10 mm, foot height 90 mm) equipped with pleated filter paper (e.g., No. 2 300 mm manufactured by ADVANTEC), and the stirred liquid is filtered for 5 minutes. The total weight (g) of the filtrate is measured, and the filtration rate of the water-absorbing resin after swelling in pure water for 20 hours is calculated based on the following formula: After swelling in pure water for 20 hours, filtration rate (%) = (total weight of filtrate (g) / 600 (g)) × 100.

[0025] The filtration rate of the water absorbent resin after swelling in pure water for 20 hours can be adjusted by, for example, adjusting the degree of crosslinking of the water absorbent resin such as the amount of an internal crosslinking agent or the amount of a surface crosslinking agent or conditions in a heat treatment step, and by adjusting the particle size of the water absorbent resin.

[0026] <Filtration rate after swelling in pure water for 10 minutes> The water absorbent resin has a filtration rate (%) after swelling in pure water for 10 minutes of preferably 70% or less, more preferably 60% or less, even more preferably 50% or less, even more preferably 40% or less, and particularly preferably 35% or less. If the filtration rate after swelling in pure water for 10 minutes measured under conditions of a shorter swelling time than the filtration rate after swelling in pure water for 20 hours is 50% or less, the water absorbent resin has better handleability after absorbing liquid in a short time (10 minutes) in the presence of solid and liquid. In this specification, the "filtration rate after swelling in pure water for 10 minutes" may be referred to as the "10-minute filtration rate".

[0027] The filtration rate of the water-absorbent resin after swelling in pure water for 10 minutes was measured as follows. 600 g of pure water is weighed out and placed in a plastic container with a diameter of 80 mm and a height of 210 mm (volume of 1 L), and a cylindrical stirrer with a length of 40 mm and a thickness of 8 mm is placed in the container and stirred at 500 rpm. 0.3 g of water-absorbent resin is placed in the container (in the weighed pure water) and stirred at 500 rpm for 10 minutes. After stirring, the stirred liquid is evenly placed in three funnels (inverted cone-shaped main body inlet diameter φ140 mm, main body height 120 mm, foot diameter φ10 mm, foot height 90 mm) equipped with pleated filter paper (e.g., No. 2 300 mm manufactured by ADVANTEC), and the stirred liquid is filtered for 5 minutes. The total weight (g) of the filtrate is measured, and the filtration rate of the water-absorbent resin after swelling in pure water for 10 minutes is calculated based on the following formula: After swelling in pure water for 10 minutes, filtration rate (%) = (total weight of filtrate (g) / 600 (g)) × 100.

[0028] The filtration rate of the water absorbent resin after swelling in pure water for 10 minutes can be adjusted by, for example, adjusting the degree of crosslinking of the water absorbent resin such as the amount of an internal crosslinking agent or the amount of a surface crosslinking agent or conditions in a heat treatment step, and by adjusting the particle size of the water absorbent resin.

[0029] <Handling after swelling in pure water> In this specification, the handleability of a water-absorbent resin after absorbing liquid can be evaluated by the handleability after swelling in pure water. Specifically, a water-absorbent resin that has good handleability after swelling in pure water when swollen 100 times can be said to be a water-absorbent resin that has excellent handleability after absorbing liquid. The method for evaluating the handleability after swelling 100 times in pure water is as follows. 0.5g of water-absorbent resin is weighed out and placed in the center of a glass petri dish with a diameter of 90mm and a height of 15mm, then 50g of pure water is poured into the glass petri dish and left to stand for 10 minutes. After standing, the glass petri dish is slowly turned over over a period of about 3 seconds, and left to stand for 10 seconds in the upside-down state. If the water-absorbent resin falls after absorbing water, it is judged as × (bad), and if it does not fall, it is judged as ○ (good).

[0030] In addition to the handleability after swelling 100 times in pure water, the water absorbent resin preferably has good handleability after swelling 75 times, more preferably has good handleability after swelling 67 times, even more preferably has good handleability after swelling 50 times, and particularly preferably has good handleability after swelling 10 times. The handleability of the water absorbent resin at different swelling ratios can be evaluated by the same operations and criteria as the above-mentioned method for evaluating the handleability after swelling 100 times in pure water, except that the amount of the water absorbent resin is changed to 5 g (10 times), 1 g (50 times), 0.75 g (67 times), and 0.67 g (75 times).

[0031] A water absorbent resin having good handleability over a wide range of swelling ratios can be said to be a water absorbent resin particularly suitable for use as a fixative in industrial applications, particularly for use as a fixative for wet loose matter, bedding material, solidification of waste liquid, etc., since there is a wider range of the amount of water absorbent resin to be added in order to obtain the effect of the present application (improved handleability after absorbing liquid) and there is a possibility that mixing work after absorbing liquid becomes unnecessary, and so on, and therefore there are fewer restrictions on use.

[0032] <crc>(NWSP 241.0.R2(15)) "CRC" is an abbreviation for Centrifuge Retention Capacity, and means the water absorption capacity of a water-absorbent resin without load (sometimes referred to as "water absorption capacity").

[0033] Specifically, 0.2 g of a water-absorbing agent or a water-absorbing resin is placed in a nonwoven bag, and then the bag is immersed in a large excess of 0.9% by mass of sodium chloride aqueous solution for 30 minutes to allow the water-absorbing agent or the water-absorbing resin to freely swell, and then the bag is dehydrated using a centrifuge (centrifugal force: 250 G), after which the absorbency (unit: g / g) is measured.

[0034] The water absorbent resin has a CRC of preferably 30 g / g or more, more preferably 33 g / g or more, even more preferably 35 g / g or more, even more preferably 38 g / g or more, and particularly preferably 40 g / g or more. A water absorbent resin having a CRC of 30 g / g or more is more sticky, that is, has better handling properties. The upper limit of the CRC is not particularly limited, but can be, for example, 55 g / g or less.

[0035] <Mass average particle diameter (D50)>(NWSP 220.0.R2(15)) In this specification, "D50" refers to the mass average particle diameter of a water absorbent resin (water absorbent resin powder) obtained through a drying process described later, and may be the mass average particle diameter of a water absorbent resin (water absorbent resin powder) obtained through surface crosslinking, granulation, rectification processes, etc.

[0036] The present water absorbent resin has a mass average particle diameter (D50) of preferably 200 μm to 800 μm, more preferably 200 μm to 600 μm, further preferably 250 μm to 500 μm, and particularly preferably 300 μm to 450 μm. According to the above constitution, there is an advantage that the water absorbent resin has a sufficient absorption speed in the coexistence of solid and liquid, and generates little dust.

[0037] The specific mass-average particle diameter (D50) of the water-absorbent resin is measured in a manner similar to “(3) Mass-Average Particle Diameter (D50) and Logarithmic Standard Deviation (σζ) of Particle Diameter Distribution” described in U.S. Pat. No. 7,638,570.

[0038] <Moisture absorption blocking rate> The water absorbent resin has a moisture absorption blocking rate (%) of preferably 20% or less, more preferably 10% or less, further preferably 5% or less, and particularly preferably 0%. A water absorbent resin having a moisture absorption blocking rate of 20% or less has excellent handling properties (moisture absorption fluidity) before absorbing liquid.

[0039] The moisture absorption blocking rate of the water-absorbent resin is measured, for example, as follows. After 2 g of the water-absorbing resin is uniformly spread in an aluminum cup having a diameter of 52 mm, the cup is left to stand for 1 hour in a thermostatic chamber (PLATINOUSLUCIFER PL-2G; manufactured by Tabai Espec Co., Ltd.) at a temperature of 25°C and a relative humidity of 90±5%RH. After 1 hour has passed, the particulate water-absorbing agent or water-absorbing resin in the aluminum cup is gently transferred onto a JIS standard sieve (The IIDA TESTING SIEVE: inner diameter 80 mm) with an opening of 2000 μm (JIS 8.6 mesh), and classified for 5 seconds under the conditions of room temperature (20 to 25°C) and relative humidity of 50%RH using a low-tap type sieve shaker (ES-65 type sieve shaker manufactured by Iida Seisakusho Co., Ltd.; rotation speed 230 rpm, impact speed 130 rpm). The mass (W1 [g]) of the particulate water absorbing agent or water absorbent resin remaining on the JIS standard sieve and the mass (W2 [g]) of the particulate water absorbing agent or water absorbent resin passing through the JIS standard sieve are measured, and the moisture absorption fluidity moisture absorption blocking rate is calculated according to the following formula g-1: Moisture absorption blocking rate (BR) (mass%)={W1 / (W1+W2)}×100...formula g-1. The lower the moisture absorption blocking rate of the water-absorbent resin, the more excellent the moisture absorption fluidity of the water-absorbent resin.

[0040] 4. Method for producing water-absorbent resin Hereinafter, an example of the method for producing the present water-absorbent resin will be described in detail, but the method for producing the present water-absorbent resin is not limited thereto.

[0041] (i) Preparation of monomer aqueous solution This step is a step of preparing an aqueous solution of a monomer (hereinafter referred to as an "aqueous monomer solution"). In addition to the monomer, an internal crosslinking agent and other substances described later may be added to the aqueous monomer solution as necessary.

[0042] In this section, for the sake of convenience, an aqueous monomer solution is described, but a slurry liquid of the monomer can also be used within a range in which the water absorption performance of the water absorbent resin obtained as the final product is not reduced.

[0043] (monomer) In one embodiment of the present invention, from the viewpoint of the physical properties and productivity of the water absorbent resin, it is preferable to use a monomer containing acrylic acid and / or an acrylic acid salt as a main component as the monomer. Here, the "main component" means that the amount (content) of acrylic acid (salt) used is usually 50 mol% to 100 mol%, preferably 70 mol% to 100 mol%, more preferably 90 mol% to 100 mol%, and even more preferably substantially 100 mol% based on the total monomers (excluding the internal crosslinking agent) used in the polymerization.

[0044] The "acrylic acid" is not particularly limited, and a known acrylic acid can be used. The known acrylic acid can be obtained, for example, by collecting gaseous acrylic acid obtained by a catalytic gas phase oxidation method with a solvent such as water, and then purifying the resulting product by distillation, crystallization, or the like. The acrylic acid may contain trace amounts of components such as a polymerization inhibitor and impurities.

[0045] As the "acrylate salt", the above-mentioned acrylic acid neutralized with the following basic compound is used, but the acrylate salt may be a commercially available acrylate salt (e.g., sodium acrylate), or may be one obtained by neutralizing acrylic acid in a production plant for a water absorbent resin.

[0046] (Basic compounds) In one embodiment of the present invention, specific examples of the "basic compound" include alkali metal carbonates, alkali metal hydrogen carbonates, alkali metal hydroxides, ammonia, organic amines, and the like. Among them, from the viewpoint of the physical properties of the obtained water absorbent resin, preferably, a compound exhibiting strong basicity is selected as the basic compound. That is, more preferably, a hydroxide of an alkali metal such as sodium, potassium, or lithium, and further preferably, sodium hydroxide is used as the basic compound. Note that, from the viewpoint of handling, the basic compound is preferably made into an aqueous solution.

[0047] (neutralization) When the acrylic acid salt is neutralized in a water-absorbent resin manufacturing plant, the timing of neutralization can be the following (1) to (3): (1) neutralization of acrylic acid (before polymerization), (2) neutralization during crosslinking polymerization of acrylic acid (during polymerization), and (3) neutralization of a hydrogel-like crosslinked polymer obtained by crosslinking polymerization of acrylic acid (after polymerization). In one embodiment of the present invention, any of (1) to (3) can be selected or used in combination as the timing of neutralization. In addition, these neutralizations may be performed in a continuous manner or a batch manner, and are not particularly limited, but are preferably performed in a continuous manner from the viewpoint of production efficiency of the water-absorbent resin.

[0048] In one embodiment of the present invention, the neutralization rate of acrylic acid is appropriately set within the range of preferably 10 mol% to 90 mol%, more preferably 40 mol% to 85 mol%, further preferably 50 mol% to 80 mol%, and particularly preferably 60 mol% to 75 mol% based on the acid group of the monomer. If the neutralization rate is less than 10 mol%, the water absorption capacity may be significantly reduced. On the other hand, if the neutralization rate is more than 90 mol%, a water absorbent resin with a low moisture absorption blocking rate may not be obtained.

[0049] The range of the neutralization rate is applied to any of the neutralization before, during, and after the above-mentioned polymerization. In addition, the neutralization rate is also applied to various forms of water-absorbent resins in the manufacturing process of water-absorbent resins, including the water-absorbent resins as final products (for example, hydrogel-like crosslinked polymers after polymerization, dried polymers after drying, water-absorbent resin powders before surface crosslinking, water-absorbent resin particles after surface crosslinking, etc.). Regarding the neutralization device and neutralization conditions such as neutralization temperature and residence time, the conditions described in International Publication No. 2009 / 123197 and the like are applied to one embodiment of the present invention.

[0050] (Other monomers) In one embodiment of the present invention, a monomer other than the above-mentioned acrylic acid (salt) (hereinafter referred to as "other monomer") can be used in combination with acrylic acid (salt) as necessary. Examples of such other monomers include monomers (excluding acrylic acid) described in U.S. Patent Application Publication No. 2005 / 0215734 and the like. Such other monomers include water-soluble or hydrophobic unsaturated monomers. When other monomers are used in combination, the amount of the monomers is appropriately set within a range of preferably 30 mol % or less, more preferably 10 mol % or less, and even more preferably 5 mol % or less, based on the total monomers (excluding the internal crosslinking agent).

[0051] (Internal crosslinking agent) As the internal crosslinking agent used in one embodiment of the present invention, the internal crosslinking agents described in U.S. Patent No. 6,241,928 and the like can be applied. Among these, one or more internal crosslinking agents are selected in consideration of reactivity and the like. In addition, from the viewpoint of the water absorption performance and the like of the obtained water absorbent resin, the internal crosslinking agent is preferably a compound having two or more polymerizable unsaturated groups, more preferably a compound having thermal decomposition at the drying temperature in the drying step described below, and even more preferably a compound having two or more polymerizable unsaturated groups having a (poly)alkylene glycol structural unit.

[0052] The polymerizable unsaturated group is preferably an allyl group or a (meth)acrylate group, more preferably a (meth)acrylate group. The (poly)alkylene glycol structural unit is preferably polyethylene glycol, and the number n (average number of moles of oxyalkylene groups added) is appropriately set preferably within a range of 1 to 100, more preferably 6 to 50. Therefore, the internal crosslinking agent used in one embodiment of the present invention is preferably, for example, (poly)alkylene glycol di(meth)acrylate or (poly)alkylene glycol tri(meth)acrylate, more preferably, for example, (poly)ethylene glycol di(meth)acrylate.

[0053] The amount of the internal crosslinking agent used is suitably set within the range of preferably 0.0001 mol% to 10 mol%, more preferably 0.001 mol% to 1 mol%, and even more preferably 0.01 mol% to 0.07 mol% based on the total amount of monomers. By setting the amount of the internal crosslinking agent used within the above range, a water-absorbent resin having a desired water-absorbing performance can be obtained. On the other hand, if it is outside the above range, an increase in water-soluble content due to a decrease in gel strength, a decrease in water absorption capacity, and a decrease in handleability after absorption are observed, which is not preferable.

[0054] In one embodiment of the present invention, a method is preferably adopted in which the internal crosslinking agent is added in advance when preparing the monomer aqueous solution, and crosslinking reaction (crosslinking polymerization) is carried out simultaneously with the polymerization reaction. However, the present invention is not limited to such a method, and a method may be adopted in which polymerization is carried out without adding an internal crosslinking agent, and then crosslinking is carried out by adding an internal crosslinking agent during or after the polymerization. These methods may also be used in combination.

[0055] (Other substances added to the aqueous monomer solution) In one embodiment of the present invention, from the viewpoint of improving the physical properties of the resulting water-absorbent resin, the following substances can be added at one or more of the following points: when preparing the monomer aqueous solution, during the polymerization process, and after the polymerization process. The substances are not particularly limited, and examples thereof include hydrophilic polymers such as starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol, polyacrylic acid (salt), and crosslinked polyacrylic acid (salt). Alternatively, the substances may be compounds such as carbonates, azo compounds, foaming agents such as air bubbles, surfactants, and chain transfer agents. These substances may be added alone or in combination of two or more.

[0056] The amount of the hydrophilic polymer added is appropriately set within a range of preferably 50% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less (lower limit: 0% by mass) based on the total amount of the monomers (including other monomers). The amount of the compound added is appropriately set within a range of preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less (lower limit: 0% by mass) based on the total amount of the monomers (including other monomers).

[0057] When a water-soluble resin or a water-absorbent resin is used as the hydrophilic polymer, a graft polymer or a water-absorbent resin composition (e.g., a starch-acrylic acid polymer, a PVA-acrylic acid polymer, etc.) is obtained, and these polymers and water-absorbent resin compositions are also included in the category of the water-absorbent resin of one embodiment of the present invention.

[0058] (monomer component concentration) In this step, the above-mentioned components are appropriately selected according to the purpose, and a predetermined amount of each component that satisfies the above-mentioned range is mixed to prepare a monomer aqueous solution. The monomer mainly composed of acrylic acid (salt) is preferably used as an aqueous solution or in a state dissolved in a mixed solvent of water and a hydrophilic solvent, more preferably as an aqueous solution. The concentration of the monomer component in the monomer aqueous solution is not particularly limited, but is appropriately set within a range of preferably 10% by mass to 80% by mass, more preferably 20% by mass to 75% by mass, and even more preferably 30% by mass to 70% by mass, from the viewpoint of the physical properties of the water-absorbent resin.

[0059] The "monomer component concentration" is a value calculated from the following (Equation 1), and in (Equation 1), the mass of the aqueous monomer solution does not include the mass of the graft component, the water-absorbent resin, and the hydrophobic organic solvent in the reversed-phase suspension polymerization. Concentration of monomer component (mass%) = (mass of monomer component) / (mass of monomer aqueous solution) × 100 (Equation 1) (ii) Polymerization process This step is a step of polymerizing the aqueous monomer solution obtained in the aqueous monomer solution preparation step to obtain a hydrogel-like crosslinked polymer (hereinafter sometimes referred to as "hydrogel").

[0060] (Polymerization initiator) The polymerization initiator used in this step includes a thermally decomposable polymerization initiator, a photodecomposable polymerization initiator, or a redox-based polymerization initiator used in combination with a reducing agent that promotes the decomposition of these polymerization initiators. For example, the polymerization initiators described in U.S. Pat. No. 7,265,190 and the like are applied. From these, one or more polymerization initiators are selected in consideration of the polymerization form and the like. In addition, from the viewpoint of the handling of the polymerization initiator and the physical properties of the water-absorbing resin, the polymerization initiator is preferably selected from a peroxide or an azo compound, more preferably from a peroxide, and even more preferably from a persulfate.

[0061] The amount of the polymerization initiator used is appropriately set within a range of preferably 0.001 mol% to 1 mol%, more preferably 0.001 mol% to 0.5 mol%, based on the total amount of monomers (including other monomers). The amount of the reducing agent used is appropriately set within a range of preferably 0.0001 mol% to 0.02 mol%, based on the total amount of monomers (including other monomers). By setting the amounts of the polymerization initiator and reducing agent used within the ranges, a water-absorbing resin having a desired water-absorbing performance can be obtained.

[0062] The polymerization reaction of the embodiment of the present invention may be initiated by irradiation with active energy rays such as radiation, electron beams, ultraviolet rays, etc. Alternatively, the irradiation with the active energy rays may be used in combination with the polymerization initiator.

[0063] (polymerization form) The polymerization form applied in one embodiment of the present invention is not particularly limited, but examples thereof include aqueous solution polymerization, reversed-phase suspension polymerization, spray polymerization, droplet polymerization, bulk polymerization, and precipitation polymerization. Among these, in consideration of the controllability of polymerization and the water absorption performance of the water-absorbing resin, preferably aqueous solution polymerization or reversed-phase suspension polymerization, more preferably aqueous solution polymerization, and even more preferably continuous aqueous solution polymerization is selected. Specific examples of continuous aqueous solution polymerization include continuous belt polymerization described in U.S. Pat. No. 4,893,999 and continuous kneader polymerization described in U.S. Pat. No. 6,987,151. By these continuous aqueous solution polymerizations, the water-absorbing resin can be produced with high productivity.

[0064] In one embodiment of the present invention, preferred forms of the continuous aqueous solution polymerization include "high-temperature initiation polymerization", "high-concentration polymerization", and "foaming polymerization". These polymerization forms can be carried out alone or in combination of two or more. The "high-temperature initiation polymerization" refers to a polymerization form in which the temperature of the aqueous monomer solution at the start of polymerization is preferably 30°C or higher, more preferably 35°C or higher, even more preferably 40°C or higher, and particularly preferably 50°C or higher (the upper limit is the boiling point of the aqueous monomer solution). The "high-concentration polymerization" refers to a polymerization form in which the concentration of the aqueous monomer solution at the start of polymerization is preferably 30% by mass or higher, more preferably 35% by mass or higher, even more preferably 40% by mass or higher, and particularly preferably 45% by mass or higher (the upper limit is the saturated concentration). The "foaming polymerization" refers to a form in which polymerization is carried out by dispersing bubbles (particularly the inert gas described below) in the aqueous monomer solution.

[0065] Although each of the above polymerization forms can be carried out under an air atmosphere, from the viewpoint of preventing coloration of the obtained water absorbent resin, it is preferably carried out under an inert gas atmosphere such as nitrogen or argon (for example, oxygen concentration is 1 volume % or less). Incidentally, the dissolved oxygen in the aqueous monomer solution is also preferably sufficiently replaced with an inert gas (for example, the amount of dissolved oxygen is less than 1 mg / l).

[0066] (iii) Gel crushing process This step is a step of obtaining a particulate hydrogel (hereinafter referred to as "particulate hydrogel") by gel pulverizing the hydrogel obtained in the polymerization step. The "gel pulverization" refers to pulverizing the hydrogel into particles using a gel pulverizer such as a kneader, meat chopper, or cutter mill. Regarding the embodiment and conditions of gel pulverization, for example, the contents described in International Publication No. 2011 / 126079 and the like are applied to one embodiment of the present invention.

[0067] In addition, when kneader polymerization is selected as the polymerization form, the polymerization step and the gel crushing step are carried out simultaneously. In addition, when a particulate hydrogel is obtained in the polymerization process, such as in reversed-phase suspension polymerization or droplet polymerization, the gel crushing step may not be carried out.

[0068] Therefore, the hydrogel obtained in the polymerization step is subjected to the next step, the drying step, either in the form of particles as it is or in the form of particles obtained by gel crushing. The mass average particle diameter (D50) (defined by wet sieve classification) of the particulate hydrogel is appropriately set within a range of preferably 0.1 mm to 50 mm, more preferably 0.2 mm to 10 mm, and even more preferably 0.5 mm to 5 mm, from the viewpoint of drying efficiency.

[0069] (iv) Drying process This step is a step of drying the particulate hydrogel obtained in the polymerization step or the particulate hydrogel obtained in the gel crushing step to a resin solid content in a desired range to obtain a dried polymer. The resin solid content in the desired range is appropriately set within a range of preferably 80% by mass or more, more preferably 85% to 99% by mass, even more preferably 90% to 98% by mass, and particularly preferably 92% to 97% by mass. Here, the "resin solid content" is a value calculated from the loss on drying (the change in mass when 1 g of a sample is dried at 180°C for 3 hours), and is calculated from the following (Equation 2). Resin solid content (mass%) = (sample mass (1 g) - drying loss) / (sample mass (1 g)) × 100 (Equation 2) The drying method in one embodiment of the present invention is not particularly limited, and examples thereof include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, high humidity drying using high temperature water vapor, etc. Among these, from the viewpoint of drying efficiency, hot air drying is preferably selected, and more preferably band drying in which hot air drying is performed on a ventilation belt is selected.

[0070] The drying temperature in this step is not particularly limited, but is appropriately set within a range of preferably 120°C to 250°C, more preferably 150°C to 200°C from the viewpoint of drying efficiency and color tone of the water-absorbent resin. The drying time is appropriately set within a range of preferably 10 minutes to 120 minutes, more preferably 20 minutes to 90 minutes, and further preferably 30 minutes to 60 minutes. By setting the drying temperature and drying time within the range, the polymer chains inside the water-absorbent resin can be changed and damage can be reduced, so that a water-absorbent resin with high physical properties in which the increase in water-soluble content is suppressed can be obtained. That is, by setting the drying temperature and drying time within the range, the CRC and Ext of the water-absorbent resin can be set to a desired range. The drying temperature is usually specified by the temperature of the heat medium (for example, in the case of hot air drying, it is specified by the temperature of the hot air), but in the case of drying that cannot be specified by the temperature of the heat medium such as microwave drying, it is specified by the temperature of the particulate hydrous gel. The drying temperature may be a constant temperature or may be appropriately changed during drying.

[0071] Drying conditions other than the drying temperature and drying time may be appropriately set depending on the moisture content of the particulate hydrogel, the amount of the particulate hydrogel to be supplied to the drying step, the target resin solid content, etc. When band drying is selected, for example, the conditions described in International Publication No. 2006 / 100300 and the like are applied to one embodiment of the present invention.

[0072] (v) Grinding process, classification process This step is a step of pulverizing the dried polymer obtained in the drying step (pulverizing step) and adjusting the particle size to a desired range (classifying step) to obtain a water absorbent resin powder. Note that this pulverizing step differs from the gel pulverizing step (iii) in that the dried polymer to be pulverized has been subjected to a drying step. Note that in this specification, the particulate water absorbent resin that has been subjected to a drying step before being subjected to surface crosslinking is conveniently referred to as a "water absorbent resin powder".

[0073] The equipment (crusher) used in the pulverization step is not particularly limited, and examples thereof include high-speed rotary crushers such as roll mills, hammer mills, screw mills, and pin mills, as well as vibration mills, knuckle-type crushers, cylindrical mixers, etc. Among these, a roll mill is preferably selected because of the ease of controlling the particle size distribution.

[0074] The method of adjusting the particle size in the classification step is not particularly limited, but preferably includes sieve classification using a JIS standard sieve (JIS Z8801-1 (2000)) and air flow classification. Among them, sieve classification is preferably selected from the viewpoint of classification efficiency. Note that this step (pulverization step, classification step) is performed not only for the water absorbent resin of the final product, but also for the water absorbent resin powder before surface crosslinking and the water absorbent resin particles after surface crosslinking so as to satisfy the PSD (particle size distribution) described in the following (4-4-4). In addition to this step (pulverization step, classification step), the particle size can also be appropriately adjusted in the polymerization step (particularly in the case of reversed phase suspension polymerization or droplet polymerization), the granulation step, and the fine powder recovery step.

[0075] The water absorbent resin powder obtained in one embodiment of the present invention has a mass average particle diameter (D50) of preferably 200 μm to 800 μm, more preferably 200 μm to 600 μm, further preferably 250 μm to 500 μm, and particularly preferably 300 μm to 450 μm. The ratio of particles having a particle diameter of less than 150 μm is preferably 10 mass% or less, more preferably 5 mass% or less, and further preferably 1 mass% or less, and the ratio of particles having a particle diameter of 850 μm or more is preferably 5 mass% or less, more preferably 3 mass% or less, and further preferably 1 mass% or less. In any case, the lower limit of the ratio of these particles is preferably as small as possible, and 0 mass% is desirable, but it may be about 0.1 mass%. Furthermore, the logarithmic standard deviation (σζ) of the particle size distribution is preferably 0.20 to 0.50, more preferably 0.25 to 0.40, and further preferably 0.27 to 0.35.

[0076] The particle sizes are measured using standard sieves in accordance with the measurement methods disclosed in US Pat. No. 7,638,570 and EDANA ERT420.2-02.

[0077] The above-mentioned particle size is also applied to the water absorbent resin particles after surface cross-linking and the water absorbent resin as a final product. Therefore, in order to maintain the particle size in the above-mentioned range in the water absorbent resin particles, it is preferable that the water absorbent resin powder is subjected to a surface cross-linking treatment (surface cross-linking step), and it is more preferable that the particle size of the water absorbent resin particles is adjusted by providing a particle size adjustment step after the surface cross-linking step.

[0078] (vi) Surface crosslinking process This step is carried out for the purpose of improving the water absorption rate of the water absorbent resin powder after drying and classification, and is a step of further providing a portion with high crosslink density on the surface layer (a portion from the surface of the water absorbent resin powder to a depth of several tens of μm inside) of the water absorbent resin powder obtained through each of the steps described above, and is composed of, for example, a mixing step, a heat treatment step, and a cooling step. In the surface crosslinking step, radical crosslinking and / or monomer polymerization in the surface layer of the water absorbent resin powder, a crosslinking reaction between the surface layer of the water absorbent resin powder and a surface crosslinking agent, etc. are carried out to obtain surface crosslinked water absorbent resin particles. In this specification, the particulate water absorbent resin after surface crosslinking is conveniently referred to as "water absorbent resin particles".

[0079] (vi-1) Mixing process This step is a step of mixing a water absorbent resin powder and a solution containing a surface cross-linking agent (hereinafter, referred to as a "surface cross-linking agent solution") in a mixer to obtain a humidified mixture.

[0080] (Surface cross-linking agent) The surface crosslinking agent used in one embodiment of the present invention is not particularly limited, but includes organic or inorganic surface crosslinking agents. Among them, from the viewpoint of the physical properties of the obtained water-absorbent resin and the handling of the surface crosslinking agent, an organic surface crosslinking agent that reacts with a carboxyl group is preferred. For example, the surface crosslinking agents described in U.S. Pat. No. 7,183,456 and the like are applied. Among these, one or more surface crosslinking agents are selected in consideration of reactivity and the like. In addition, from the viewpoint of the handling of the surface crosslinking agent and the absorption performance of the water-absorbent resin, preferably, a compound having two or more functional groups that react with a carboxyl group and an organic compound that forms a covalent bond by reaction with the carboxyl group is selected. Specific examples of such organic compounds include polyhydric alcohol compounds, epoxy compounds, polyvalent amine compounds, condensates of polyvalent amine compounds and haloepoxy compounds, oxazoline compounds, oxazolidinone compounds, alkylene carbonate compounds, polyvalent glycidyl compounds, oxetane compounds, vinyl ether compounds, and cyclic urea compounds.

[0081] The amount of the surface crosslinking agent used (the total amount when a plurality of agents are used) is appropriately set within a range of preferably 0.01 to 10 parts by mass, more preferably 0.01 to 5 parts by mass, relative to 100 parts by mass of the water absorbent resin powder. By setting the amount of the surface crosslinking agent used within the range, an optimal crosslinked structure can be formed in the surface layer of the water absorbent resin powder, and a water absorbent resin with high physical properties can be obtained.

[0082] The surface cross-linking agent is preferably added to the water absorbent resin powder as an aqueous solution. In this case, the amount of water used is appropriately set within a range of preferably 0.1 to 20 parts by mass, more preferably 0.3 to 15 parts by mass, and further preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the water absorbent resin powder. By setting the amount of water used within the range, the handleability of the surface cross-linking agent solution is improved, and the surface cross-linking agent can be evenly mixed with the water absorbent resin powder.

[0083] In addition, each of the additives added in the "re-moistening step" described later can be added by mixing it with the surface cross-linking agent (aqueous solution) in an amount within the range of 5 parts by mass or less, or can be added separately in a mixing step.

[0084] (Mixing method)

[0213] A method of mixing the water absorbent resin powder and a surface crosslinking agent solution is not particularly limited, but a method of preparing a surface crosslinking agent solution in advance, and mixing the solution by preferably spraying or dropping, more preferably spraying, to the water absorbent resin powder is selected.

[0085] The mixing device for carrying out the mixing is not particularly limited, but it is preferable that the mixing device has a large mixing power in order to mix the water absorbent resin powder and the surface crosslinking agent uniformly and reliably. As the mixing device, a high-speed stirring type mixer is preferable, and a high-speed stirring type continuous mixer is more preferable. Specifically, a cylindrical mixer, a double-walled cone type mixer, a V-shaped mixer, a ribbon type mixer, a screw type mixer, a fluidized furnace rotary disk type mixer, an air flow type mixer, a double-arm type kneader, an internal mixer, a grinding type kneader, a rotary mixer, a screw type extruder, a turbulizer, etc. are selected.

[0086] When carrying out the mixing, the temperature of the water absorbent resin powder to be supplied to this step is appropriately set within a range of preferably 35° C. to 80° C., more preferably 35° C. to 70° C., and further preferably 35° C. to 60° C., in consideration of the mixability with the surface crosslinking agent solution, the coagulation property of the humidified mixture, etc. Also, the mixing time is appropriately set within a range of preferably 1 second to 1 hour, more preferably 5 seconds to 10 minutes.

[0087] (vi-2) Heat treatment process This step is a step of heat-treating the humidified mixture obtained in the mixing step to obtain water-absorbent resin particles.

[0088] (Heat treatment method) The method for heating the humidified mixture is not particularly limited, and the humidified mixture may be heated in a stationary state or may be heated using a mixing means such as stirring. From the viewpoint of being able to heat the entire humidified mixture evenly, it is preferable to heat it while stirring and mixing. In addition, preferred examples of the apparatus used in this step include a mortar mixer, a paddle dryer, a multi-fin processor, and a tower dryer.

[0089] The heating temperature in this step is not particularly limited and may be set depending on the type and amount of the surface cross-linking agent used, the absorption performance of the target water absorbent resin, etc., but may be appropriately set as the heat medium temperature preferably within the range of 70° C. to 250° C., more preferably 90° C. to 210° C. In addition, the heating time is also not particularly limited, but may be appropriately set preferably within the range of 1 minute to 2 hours.

[0090] (vi-3) Cooling process This step is an optional step that is performed as necessary after the heat treatment step. In this step, the water absorbent resin particles undergoing the surface cross-linking reaction are forcibly cooled, and the surface cross-linking reaction is quickly terminated.

[0091] (Cooling method) The method for cooling the water-absorbent resin particles is not particularly limited, and the water-absorbent resin particles may be cooled in a stationary state, or may be cooled using a mixing means such as stirring. From the viewpoint of being able to cool the water-absorbent resin particles uniformly and quickly throughout, it is preferable to cool the particles while stirring and mixing. In addition, preferred examples of the apparatus used in this step include a paddle dryer, a multi-fin processor, and a tower dryer.

[0092] The cooling temperature in this step is not particularly limited and may be set depending on the heat treatment temperature, the absorption performance of the target water absorbent resin, etc., but may be appropriately set within a range of preferably 40°C to 100°C, more preferably 40°C to 90°C, and further preferably 40°C to 70°C as the refrigerant temperature.

[0093] (vii) Rehumidification process This step is an optional step of adding at least one additive selected from the group consisting of inorganic powder, polyvalent metal salt compound, cationic polymer, inorganic reducing agent, α-hydroxycarboxylic acid compound, deodorant, other antibacterial agent, and aqueous liquid containing a bactericidal component to the water-absorbent resin particles obtained in the surface cross-linking step. Note that, in the present specification, the water-absorbent resin particles to be subjected to the re-moistening step may be referred to as a particulate water-absorbing agent.

[0094] In addition, since the additive is added in the form of an aqueous solution or a slurry, the water absorbent resin particles are swollen again with water. For this reason, this process is called a "re-wetting process". In addition, the additive can be mixed with the water absorbent resin powder simultaneously with the surface cross-linking agent (aqueous solution).

[0095] (Inorganic powder) The water-absorbent resin according to one embodiment of the present invention may include a plurality of inorganic powders arranged on the surface of the water-absorbent resin. As the inorganic powder, a water-insoluble inorganic powder is preferable, and a hydrophilic and water-insoluble inorganic powder is more preferable. Examples of such inorganic powders include metal oxides such as silica (silicon dioxide) such as amorphous silica and titanium oxide; composite hydrated oxides containing zinc and silicon or zinc and aluminum (for example, as exemplified in International Publication No. 2005 / 010102); polyvalent metal compounds such as aluminum sulfate, potassium alum, ammonium alum, sodium alum, (poly)aluminum chloride, and hydrates thereof; polycation compounds such as polyethyleneimine, polyvinylamine, and polyallylamine; silicic acid (salt) such as natural zeolite and synthetic zeolite, kaolin, talc, clay, bentonite, calcium phosphate, barium phosphate, silicic acid or its salt, clay, diatomaceous earth, silica gel, zeolite, bentonite, hydroxyapatite, hydrotalcite, vermiculite, perlite, isolite, activated clay, silica sand, silica stone, strontium ore, fluorite, bauxite, etc. Among these, silicon dioxide and silicic acid (salt) are more preferable. These inorganic powders may be used alone or in combination of two or more.

[0096] The method of disposing the inorganic powder on the surface of the water absorbent resin is not particularly limited, and for example, the inorganic powder can be disposed on the surface of the water absorbent resin by mixing (dry blending) the water absorbent resin and the inorganic powder, and can also be added as an aqueous solution or by thermal fusion. The inorganic powder may be disposed on the surface of the water absorbent resin by carrying out these methods alone, or a plurality of methods may be combined (for example, an aqueous solution containing another inorganic powder may be further added and mixed to a blend obtained by dry blending the water absorbent resin and the inorganic powder).

[0097] When the water absorbent resin contains inorganic powder arranged on the surface of the polymer particle, the content of the inorganic powder may be 0.05% by mass or more, 0.1% by mass or more, 0.15% by mass or more, or 0.2% by mass or more, based on the total mass of the water absorbent resin. The content of the inorganic powder may be 5.0% by mass or less, 3.0% by mass or less, 1.0% by mass or less, or 0.5% by mass or less. If the content of the inorganic powder is 0.05% by weight or more, a water absorbent resin having excellent powder flowability during moisture absorption can be obtained. Also, if the content of the inorganic powder is 5.0% by weight or less, there is no risk of impairing the water absorption performance of the water absorbent resin.

[0098] The inorganic powder usually has a minute size compared to the size of the water-absorbent resin. For example, the average particle size of the inorganic powder is 0.001 to 200 μm, more preferably 0.005 to 50 μm, and further preferably 0.01 to 10 μm. The average particle size can be measured by a pore electrical resistance method (Coulter counter method) or a laser diffraction / scattering method depending on the characteristics of the particles.

[0099] (Polyvalent metal salt and / or cationic polymer) In one embodiment of the present invention, from the viewpoint of improving the water absorption rate, moisture absorption fluidity, etc. of the obtained water absorbent resin, a polyvalent metal salt and / or a cationic polymer may be added.

[0100] As the polyvalent metal salt and / or cationic polymer, specifically, the compounds disclosed in “[7] Polyvalent metal salt and / or cationic polymer” of WO 2011 / 040530 and the amounts used thereof are applicable to one embodiment of the present invention.

[0101] (Inorganic reducing agent) In one embodiment of the present invention, from the viewpoints of the color tone (prevention of coloration) of the obtained water-absorbent resin, prevention of deterioration, reduction of residual monomers, and the like, an inorganic reducing agent may be added.

[0102] Specifically, the inorganic reducing agent may be the compound disclosed in “(3) Inorganic Reducing Agent” of WO 2011 / 040530 and the amount of use thereof.

[0103] (α-Hydroxycarboxylic acid compounds) In one embodiment of the present invention, an α-hydroxycarboxylic acid may be added from the viewpoint of the color tone (prevention of coloring) of the obtained water absorbent resin, etc. The "α-hydroxycarboxylic acid compound" refers to a carboxylic acid having a hydroxyl group in the molecule or a salt thereof, and is a hydroxycarboxylic acid having a hydroxyl group at the α-position.

[0104] Specifically, the α-hydroxycarboxylic acid compound and the amount of use thereof disclosed in “[6] α-hydroxycarboxylic acid compound” of WO 2011 / 040530 are applicable to one embodiment of the present invention.

[0105] (viii) Addition of other additives In one embodiment of the present invention, additives other than the additives described above can be added to the water-absorbing resin to add various functions.Specific examples of other additives include surfactants, compounds having phosphorus atoms, oxidizing agents, organic reducing agents, water-insoluble inorganic fine particles, organic powders such as metal soaps, pulp and thermoplastic fibers, fragrances, foaming agents, pigments, dyes, plasticizers, adhesives, fertilizers, salts, hydrophilic polymers such as polyethylene glycol and polyethyleneimine, hydrophobic molecules such as paraffin, thermoplastic resins such as polyethylene and polypropylene, and thermosetting resins such as polyester resins and urea resins.The surfactant is preferably a compound disclosed in International Publication No. 2005 / 075070.

[0106] The amount of the additive used (added amount) is not particularly limited since it is appropriately determined depending on the application, but is preferably 3 parts by mass or less, more preferably 1 part by mass or less, relative to 100 parts by mass of the water absorbent resin powder. In addition, the additive can also be added in a step different from the above step.

[0107] (ix) Other processes In one embodiment of the present invention, in addition to the above-mentioned steps, a granulation step, a sizing step, a fine powder removal step, a fine powder reuse step, etc., can be provided as necessary. In addition, one or more steps such as a transport step, a storage step, a packaging step, and a storage step may be further included. The "sizing step" includes a fine powder removal step after the surface crosslinking step, and a step of classifying and pulverizing the water absorbent resin when the water absorbent resin aggregates and exceeds a desired size. In addition, the "fine powder reuse step" includes a form in which the fine powder is added as it is to the monomer or the polymer gel before drying (recycling to the polymerization step or gel crushing step) as in one embodiment of the present invention, and also includes a step of making the fine powder into a large hydrous gel and adding it to any step in the production process of the water absorbent resin.

[0108] [5. Fixative] In one embodiment of the present invention, a fixing agent containing the water-absorbent resin is provided. The fixing agent according to one embodiment of the present invention (hereinafter, may be referred to as the fixing agent) contains the water-absorbent resin, and therefore has excellent handling properties after absorbing liquid in the presence of solid and liquid. In this specification, the fixing agent is intended to mean an agent that has the effect of absorbing moisture and turning into a solid (reducing the moisture content) in the presence of solid and liquid, and has the effect of binding and fixing the solid components. The fixing agent can also be called a binder.

[0109] The uses of the fixing agent are not particularly limited, and the fixing agent can be suitably used for various uses, such as for moist bulk materials, bedding materials, solidification of waste liquids, seed coating materials, drip absorbents, solidification of surplus soil, water-absorbing sandbags, soil water retention agents, etc. More preferably, the fixing agent can be suitably used for moist bulk materials, bedding materials, and solidification of waste liquids.

[0110] (Fixing agent for moist bulk materials) The fixing agent can be suitably used as a fixing agent for wet bulk materials. In this specification, bulk materials refer to powder or granular cargoes transported in trucks or bulk tankers without packaging, such as coal, coke, iron ore, limestone, sintered ore, steel mill dust, wood chips, wood pellets, RDF, RPF, and other solid fuels and steel raw materials.

[0111] Since the bulk materials described above are usually stored and transported outdoors (in an unsheltered space), they contain a lot of moisture due to precipitation, watering to prevent dust, etc. In other words, they are in a hydrated state (wet bulk materials). Wet bulk materials become muddy and fluid (slurry-like) containing a lot of moisture, which creates the problem that it is difficult to transport them from storage locations (ship holds, raw material yards, etc.).

[0112] By contacting the fixing agent for hydrated bulk materials according to one embodiment of the present invention with hydrated bulk materials, the water absorbing action of the water absorbent resin contained in the fixing agent can remove water from the hydrated bulk materials in a slurry state, and the handling (e.g., transportability) of the bulk materials (hydrated bulk materials from which water has been removed) can be improved. Furthermore, since the fixing agent for hydrated bulk materials according to one embodiment of the present invention is excellent in handling after absorbing liquid (i.e., excellent in cohesiveness), scattering and dust generation can be suppressed when transporting bulk materials using a belt conveyor or the like. As described above, the fixing agent can be suitably used as a fixing agent for hydrated bulk materials.

[0113] That is, in one embodiment of the present invention, there is provided a method for modifying hydrated rose product, which comprises a step of contacting a fixative for hydrated rose product with the hydrated rose product. Here, "modification" refers to removing water from the hydrated rose product to improve its handleability. Note that one embodiment of the present invention may also include a method for producing modified hydrated rose product, which includes the present modification method as one step.

[0114] The amount of fixative used for moist bulk products according to one embodiment of the present invention may be appropriately determined based on the storage environment of the moist bulk products, the moisture content, etc. For example, the moisture content of the moist bulk products may be estimated based on the number of days since precipitation or watering, the humidity of the storage environment, etc., and the amount of fixative used may be adjusted.

[0115] The fixing agent for moist bulk matter according to one embodiment of the present invention may optionally contain, in addition to the water-absorbent resin, a polymer flocculant or the like, within a range in which the effects of the present application are not impaired.

[0116] (Fixing agent for bedding) The fixing agent can also be suitably used as a fixing agent for bedding. In this specification, bedding refers to a material that is laid on the floor of a livestock house for the purpose of managing human waste in a livestock house (e.g., cows, horses, pigs, etc.). The bedding can also be called a human waste treatment material.

[0117] When used in livestock sheds, bedding needs to be replaced frequently, every few days, from the viewpoint of hygiene management. Therefore, bedding is required to have excellent handleability from the viewpoint of reducing the burden of replacement work. In addition, bedding is required to not generate dust so as not to damage the respiratory organs of livestock and workers.

[0118] The fixing agent for bedding according to one embodiment of the present invention contains the water-absorbent resin, and therefore can treat livestock manure (especially the water contained in the manure), and also has excellent handleability of the solidified material after absorbing the liquid (i.e., excellent cohesiveness). Therefore, the bedding can be easily replaced, and dust is unlikely to be generated, so there is no risk of damaging the respiratory organs of livestock or workers. In addition, it can be fermented after use and used as compost.

[0119] The fixing agent for bedding materials according to one embodiment of the present invention may optionally contain, in addition to the water-absorbent resin, within a range that does not impair the effects of the present application, wood-based bedding materials such as sawdust, chips, thinned wood, etc.; herbaceous bedding materials such as wheat straw, rice straw, poor pasture grass, etc.; paper materials such as paper and pulp, as well as paper-based bedding materials such as waste paper such as magazines, newspapers, cardboard, and crushed paper; porous compounds such as activated carbon and zeolite; extracts from natural products such as humic acid, yucca extract, flavonoids, and deodorizing / deodorizing agents such as microorganisms such as dried yeast cells; and the like.

[0120] (Fixing agent for solidifying waste liquid) The fixative of the present invention can also be suitably used as a fixative for solidifying waste liquids. The waste liquids for which the fixative of the present invention can be used are not particularly limited, but examples thereof include industrial waste liquids, waste liquids generated during food manufacturing, waste liquids generated after food consumption, fecal waste liquids, radioactive waste liquids, beverage waste liquids, and muddy waters containing sludge. EXAMPLES

[0121] The present invention will be described in more detail with reference to the following Examples and Comparative Examples, but the present invention is not limited thereto, and examples obtained by appropriately combining the technical means disclosed in each Example are also included in the scope of the present invention. In the Examples, the indications "parts" or "%" may be used, but unless otherwise specified, they represent "parts by mass" or "% by mass". In addition, the electric equipment used in the Examples and Comparative Examples (including the measurement of the physical properties of the water-absorbent resin) was powered by a 200V or 100V power source unless otherwise noted. In addition, the various physical properties of the water-absorbent resin of the present invention were measured under the conditions of room temperature (20°C to 25°C) and a relative humidity of 50% RH unless otherwise noted. In addition, as the pure water, water with an electric conductivity (μS / cm) of 10 or less at 25°C was used.

[0122] [Method of measuring physical properties of water-absorbent resin] The methods for measuring the physical properties of the water-absorbent resin in the examples will be described below.

[0123] <Filtration rate after swelling in pure water for 20 hours> The filtration rate of the water-absorbent resin after swelling in pure water for 20 hours was measured as follows. 600 g of pure water was weighed out into a plastic container with a diameter of 80 mm and a height of 210 mm (volume 1 L), and a cylindrical stirrer with a length of 40 mm and a thickness of 8 mm was placed in the container and stirred at 500 rpm. 0.3 g of water-absorbing resin was put into the container (in the weighed pure water) and stirred at 500 rpm for 10 minutes. Then, stirring was stopped and the mixture was left to stand for 20 hours. After being left to stand, the mixture was stirred at 500 rpm for another 10 minutes. The liquid after stirring was evenly placed into three funnels (inverted cone-shaped main body inlet diameter φ140 mm, main body height 120 mm, foot diameter 10 mm, foot height 90 mm) equipped with pleated filter paper (e.g., No. 2 300 mm manufactured by ADVANTEC), and the liquid after stirring was filtered for 5 minutes. The total weight (g) of the filtrate was measured, and the filtration rate of the water-absorbing resin after swelling in pure water for 10 minutes was calculated based on the following formula: After swelling in pure water for 20 hours, filtration rate (%) = (total weight of filtrate (g) / 600 (g)) × 100.

[0124] <Filtration rate after swelling in pure water for 10 minutes> The filtration rate of the water-absorbent resin after swelling in pure water for 10 minutes was measured as follows. 600 g of pure water was weighed out and placed in a plastic container with a diameter of 80 mm and a height of 210 mm (volume 1 L), and a cylindrical stirrer with a length of 40 mm and a thickness of 8 mm was placed in the container and stirred at 500 rpm. 0.3 g of water-absorbent resin was placed in the container (in the weighed pure water) and stirred at 500 rpm for 10 minutes. After stirring, the stirred liquid was evenly placed in three funnels (inverted cone-shaped main body inlet diameter φ140 mm, main body height 120 mm, foot diameter φ10 mm, foot height 90 mm) equipped with pleated filter paper (e.g., No. 2 300 mm manufactured by ADVANTEC), and the stirred liquid was filtered for 5 minutes. The total weight (g) of the filtrate was measured, and the filtration rate of the water-absorbent resin after swelling in pure water for 10 minutes was calculated based on the following formula: After swelling in pure water for 10 minutes, filtration rate (%) = (total weight of filtrate (g) / 600 (g)) × 100.

[0125] <Evaluation of handling after swelling in pure water> (Evaluation of handling after swelling 100 times in pure water) 0.5 g of water-absorbent resin was weighed out and placed in the center of a glass petri dish with a diameter of 90 mm and a height of 15 mm, and then 50 g of pure water was poured into the glass petri dish and left to stand for 10 minutes. After standing, the glass petri dish was slowly turned over over a period of about 3 seconds and left to stand for 10 seconds in the upside-down state. If the water-absorbent resin after absorbing water fell, it was judged as ×, and if it did not fall, it was judged as ◯.

[0126] After the evaluation, the water-absorbent resin after absorbing water that dropped from the glass petri dish (i.e., the water-absorbent resin rated as x) was in a loose powder form, and when scooped up with a spatula, it was likely to fall off the spatula, and handling during transportation was poor. On the other hand, the water-absorbent resin after absorbing water that did not drop from the glass petri dish after the evaluation (i.e., the water-absorbent resin rated as ◯) could be easily scooped up from above the petri dish with a spatula, and even after scooping up, the water-absorbent resin was unlikely to fall apart, was unlikely to fall off the spatula, and handling during transportation was good.

[0127] (10x, 50x, 67x, 75x pure water, handling evaluation method after swelling in pure water) Except for changing the amount of the water-absorbent resin to 5 g, 1 g, 0.75 g, or 0.67 g, the evaluation was performed using the same procedures and criteria as in the evaluation method for handleability after swelling 100 times in pure water.

[0128] <crc> The method for measuring the CRC of the water-absorbent resin was as follows: 0.2 g of the water-absorbent resin was placed in a nonwoven bag, and then immersed in a large excess of 0.9% by mass sodium chloride aqueous solution for 30 minutes to allow the water-absorbent resin to freely swell, and then the water-absorbent resin was dehydrated using a centrifuge (centrifugal force: 250 G), after which the CRC was calculated as the absorption capacity (unit: g / g).

[0129] <Mass average particle diameter (D50)> The mass-average particle diameter (D50) of the water-absorbent resin was measured in the same manner as in “(3) Mass-Average Particle Diameter (D50) and Logarithmic Standard Deviation (σζ) of Particle Diameter Distribution” described in U.S. Pat. No. 7,638,570.

[0130] <Moisture absorption blocking rate> The moisture absorption blocking rate of the water-absorbent resin was measured as follows. After uniformly dispersing 2 g of the water-absorbing resin in an aluminum cup having a diameter of 52 mm, the cup was left to stand for 1 hour in a thermostatic chamber (PLATINOUSLUCIFER PL-2G; manufactured by Tabai Espec Co., Ltd.) at a temperature of 25°C and a relative humidity of 90±5%RH. After 1 hour, the particulate water-absorbing agent or water-absorbing resin in the aluminum cup was gently transferred onto a JIS standard sieve (The IIDA TESTING SIEVE: inner diameter 80 mm) with an opening of 2000 μm (JIS 8.6 mesh), and classified for 5 seconds under the conditions of room temperature (20 to 25°C) and relative humidity of 50%RH using a low-tap type sieve shaker (ES-65 type sieve shaker manufactured by Iida Seisakusho Co., Ltd.; rotation speed 230 rpm, impact speed 130 rpm). The mass (W1 [g]) of the particulate water absorbing agent or water absorbent resin remaining on the JIS standard sieve and the mass (W2 [g]) of the particulate water absorbing agent or water absorbent resin passing through the JIS standard sieve were measured, and the moisture absorption blocking rate was calculated according to the following formula g-1: Moisture absorption blocking rate (BR) (mass%) = {W1 / (W1+W2)} x 100...Equation g-1.

[0131] Example 1 A reaction solution was prepared by dissolving 4.79 g of polyethylene glycol diacrylate (average number of moles of ethylene oxide added: 9) as an internal crosslinking agent in 5,500 g of a 33 wt % aqueous solution of sodium acrylate (hydrophilic unsaturated monomer) with a neutralization rate of 75 mol %. Next, this reaction solution was degassed for 30 minutes under a nitrogen gas atmosphere (nitrogen gas was blown into this reaction solution for 30 minutes to expel dissolved oxygen in the reaction solution). Next, the reaction solution was supplied to a reactor formed by attaching a lid to a jacketed stainless steel double-arm kneader with an internal volume of 10 L having two sigma-type blades, and the system was replaced with nitrogen gas while maintaining the reaction solution at 25°C. Next, 2.4 g of ammonium persulfate and 0.12 g of L-ascorbic acid were added as polymerization initiators while stirring the reaction solution, and polymerization started about 1 minute later. Then, polymerization was carried out at 25 to 90°C, and the reaction was terminated 40 minutes after the start of polymerization, and a hydrogel-like crosslinked polymer was taken out.

[0132] The obtained hydrogel crosslinked polymer was fragmented to a diameter of about 5 mm. The fragmented hydrogel crosslinked polymer (particulate hydrogel) was spread on a wire net with a mesh size of 50 mesh (opening size of 300 μm) and dried with hot air at 170° C. for 70 minutes to obtain a dried polymer. The dried polymer was then pulverized using a vibration mill and classified to obtain an irregularly pulverized water absorbent resin powder.

[0133] 100 parts by weight of the obtained water absorbent resin powder was mixed with an aqueous surface crosslinking agent solution consisting of 0.7 parts by weight of propylene glycol, 0.02 parts by weight of ethylene glycol diglycidyl ether, 2 parts by weight of water, and 0.7 parts by weight of ethyl alcohol. The mixture was heat-treated at 185°C for 40 minutes to obtain water absorbent resin particles.

[0134] Next, 0.3 g of hydrophilic silicon dioxide (product name: Aerosil 200 (average particle size of primary particles: about 12 nm); manufactured by Nippon Aerosil Co., Ltd.) was added as an inorganic powder to 100 g of the water absorbent resin particles and mixed (dry blended) to obtain a water absorbent resin according to one embodiment of the present invention. The physical properties of the obtained water absorbent resin were measured. The results are shown in Table 1.

[0135] Example 2 291 g of acrylic acid, 0.63 g of polyethylene glycol diacrylate (average number of moles of ethylene oxide added: 9) as an internal crosslinking agent, 1.80 g of 1.0 wt% aqueous solution of trisodium diethylenetriamine pentaacetate, and 3.60 g of 1.0 wt% IRGACURE® 184 acrylic acid solution were added to a 1 L polypropylene container covered with a polystyrene foam insulation material to prepare a mixed solution (a). 247 g of 48.5 wt% aqueous solution of sodium hydroxide and 255 g of ion-exchanged water adjusted to 50°C were added to another 1 L polypropylene container covered with a polystyrene foam insulation material to prepare a mixed solution (b). While stirring the mixed solution (a) at 800 rpm using a magnetic stirrer (length 5 cm), the mixed solution (b) was quickly added and mixed to obtain an aqueous monomer solution. The temperature of the monomer aqueous solution rose to about 100°C due to the heat of neutralization and dissolution. The neutralization rate of acrylic acid was 73.5 mol%. The content of trisodium diethylenetriaminepentaacetate (chelating agent) was 0.005% by weight (50 ppm) based on the monomer solid content. Next, 1.8 g of a 3% by weight aqueous solution of sodium persulfate was added as a polymerization initiator to the monomer aqueous solution to obtain a reaction solution. After stirring the reaction solution for about 1 second, it was immediately poured into a stainless steel vat-type reaction device (bottom: 340 x 340 mm, height: 25 mm, inner surface: Teflon (registered trademark) coating) in an open-air system. At the same time, ultraviolet light was irradiated, and the polymerization reaction started about 10 seconds later. The peak temperature was then reached within about 1 minute. After 3 minutes had passed since the start of polymerization, the ultraviolet light irradiation was stopped, and the hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel") was taken out. The above series of operations were carried out in an open-air system.

[0136] Next, the hydrogel was crushed using a meat chopper (EAT-CHOPPER TYPE 12VR-400KSOX; die hole diameter: 6.4 mm, number of holes: 38, die thickness: 8 mm / manufactured by Iizuka Kogyo Co., Ltd.) to obtain a finely divided hydrogel (particulate hydrogel).

[0137] Next, the above-mentioned finely divided hydrogel was spread on a wire net having an opening of 300 μm (50 mesh) and dried with hot air at 180° C. for 45 minutes to obtain a dried polymer.

[0138] Subsequently, the obtained dried polymer was pulverized using a roll mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm. Through a series of these operations, an irregularly pulverized water absorbent resin powder having a particle size of 150 μm or more and less than 850 μm was obtained. The solid content of the water absorbent resin powder was 97% by weight. Subsequently, 3.52 parts by weight of a surface crosslinking agent solution consisting of 0.024 parts by weight of ethylene glycol diglycidyl ether, 0.5 parts by weight of propylene glycol, 2.7 parts by weight of ion-exchanged water, and 0.3 parts by weight of 1,4-butanediol was uniformly mixed with 100 parts by weight of the water absorbent resin powder, and the mixture was heat-treated at 176° C. for 40 minutes, and further sized using a JIS standard sieve with mesh sizes of 850 μm, thereby obtaining water absorbent resin particles with crosslinked surfaces.

[0139] A mixed liquid consisting of 0.1 part by weight of trisodium diethylenetriaminepentaacetate and 1 part by weight of ion-exchanged water was dropped onto 100 parts by weight of the obtained water absorbent resin particles, and mixed uniformly. After that, the mixture was left to stand in a hot air dryer at 60°C for 60 minutes, and several particles were aggregated to form a granule (hereinafter, for convenience, referred to as "water absorbent resin granules").

[0140] Next, 30 g of the water-absorbent resin granules and 10 g of glass beads having a diameter of 6 mm were placed in a glass container (diameter 6 cm, height 11 cm), and the water-absorbent resin granules were crushed using a paint shaker (product No. 488 / Toyo Seiki Seisakusho).

[0141] The disintegration was carried out by shaking the mixture in a paint shaker at 800 (cycles / min) (CP) for 30 minutes. Details of the paint shaker are disclosed in JP-A-9-235378.

[0142] After the shaking, the glass beads were removed using a JIS standard sieve with 2 mm openings to obtain a particulate water absorbing agent.

[0143] The particulate water absorbing agent was dry-mixed with 0.3 parts by weight of silicon dioxide (Aerosil 200; Nippon Aerosil Co., Ltd.) as an inorganic powder to obtain a water absorbent resin. The properties of the obtained water absorbent resin were measured. The results are shown in Table 1.

[0144] Example 3 7.5 g of polyethylene glycol diacrylate (average number of moles of ethylene oxide added: 9) was dissolved in 5500 g of an aqueous solution of sodium acrylate having a neutralization rate of 75 mol% (monomer concentration: 38% by mass) to prepare a reaction solution. Next, the reaction solution was fed into a reactor formed by attaching a lid to a jacketed stainless steel double-arm kneader having an internal volume of 10 L and two sigma-type blades, and the system was replaced with nitrogen gas while the reaction solution was kept at 30°C to remove dissolved oxygen. Next, 29.8 g of a 10% by mass aqueous solution of sodium persulfate and 1.5 g of a 1% by mass aqueous solution of L-ascorbic acid were added while stirring the reaction solution, and polymerization started about 1 minute later. The polymerization peak temperature was 86°C 17 minutes after the start of polymerization, and the hydrogel-like crosslinked polymer was taken out 60 minutes after the start of polymerization. The obtained hydrogel-like crosslinked polymer was fragmented into particles of about 1 to 4 mm.

[0145] This finely divided hydrogel crosslinked polymer (particulate hydrogel) was spread on a 50 mesh (mesh size: 300 μm) wire net and dried with hot air at 160° C. for 60 minutes to obtain a dried polymer.

[0146] The obtained dried polymer was then pulverized using a roll mill, and further classified continuously using wire mesh with openings of 450 μm and 106 μm. Particles with a size of 450 μm or more were pulverized again using a roll mill. Particles that passed through the 106 μm wire mesh accounted for 13 mass% of the total amount of particles pulverized. The water-absorbent resin fine particles that passed through the 106 μm wire mesh were mixed with the same amount of water heated to 90° C., dried again under the same conditions, and pulverized. By such operations, an irregularly pulverized water-absorbent resin powder was obtained at a yield of 98%.

[0147] Next, 100 parts by mass of the obtained water absorbent resin powder was mixed with 0.7 parts by mass of a surface cross-linking agent aqueous solution consisting of 0.1 parts by mass of ethylene glycol diglycidyl ether, 0.3 parts by mass of propylene glycol, and 0.3 parts by mass of water. The mixture was heat-treated for 20 minutes in a mortar mixer heated to 210°C to obtain surface-cross-linked water absorbent resin particles.

[0148] A mixed solution consisting of 0.01 parts by mass of sodium diethylenetriamine pentaacetate, 0.1 parts by mass of a 15% by mass aqueous solution of a leaf extract of a plant of the family Theaceae (product name: FS-80MO, sold by Shiraimatsu Shinyaku Co., Ltd. (location: 37-1 Ukawa, Minakuchi-cho, Koga-gun, Shiga Prefecture)) and 3 parts by mass of water was sprayed and mixed with 100 parts by mass of the obtained water absorbent resin particles. The obtained mixture was heated and cured for 1 hour while maintaining a moisture content of 3% by mass at 60°C, and passed through a wire mesh with an opening of 600 μm to obtain a particulate water absorbing agent. 0.3 parts by mass of fine particles of silicon dioxide (product name: Aerosil 200) as an inorganic powder was added to 100 parts by mass of the obtained particulate water absorbing agent and mixed (dry blended) to obtain a water absorbent resin containing 35% by mass of granulated particles. Each physical property of the obtained water absorbent resin was measured. The results are shown in Table 1.

[0149] Example 4 A monomer aqueous solution was prepared by mixing 67.0 parts of a 37% aqueous sodium acrylate solution, 10.2 parts of acrylic acid, 0.084 parts of polyethylene glycol diacrylate (average number of moles of ethylene oxide added: 9) and 22.0 parts of water. Nitrogen was blown into the aqueous monomer solution in a tray to reduce the dissolved oxygen in the solution to 0.1 ppm or less. The temperature of the aqueous monomer solution was then adjusted to 18°C ​​under a nitrogen atmosphere, and then 0.16 parts of a 5% aqueous sodium persulfate solution, 0.16 parts of a 5% aqueous 2,2'-azobis(2-amidinopropane) dihydrochloride solution, 0.15 parts of a 0.5% aqueous L-ascorbic acid solution and 0.17 parts of a 0.35% aqueous hydrogen peroxide solution were added dropwise in that order with stirring. Polymerization started immediately after the addition of hydrogen peroxide. Then, stirring was stopped, and the temperature of the monomer reached a peak temperature 10 minutes later. The peak temperature was 85°C. The tray was then immersed in a water bath at 80° C. and aged for 10 minutes, and the resulting transparent hydrogel-like crosslinked polymer was crushed with a meat chopper. The finely divided hydrogel crosslinked polymer was then spread on a wire net with a mesh size of 50 mesh (opening size: 300 μm) and dried with hot air at 180° C. for 30 minutes to obtain a dried polymer.

[0150] The obtained dried polymer was pulverized in a pulverizer and classified into those that passed through a 500 μm sieve and remained on a 105 μm sieve, to obtain a water-absorbent resin powder.

[0151] 100 parts of the obtained water absorbent resin powder was mixed with a composition liquid consisting of 0.05 parts of ethylene glycol diglycidyl ether, 1 part of propylene glycol, 3 parts of water and 1 part of isopropyl alcohol, and the mixture was heat-treated at 180°C for 40 minutes to obtain surface-crosslinked water absorbent resin particles.

[0152] A mixed solution consisting of 0.1 parts by weight of trisodium diethylenetriaminepentaacetate and 1 part by weight of ion-exchanged water was sprayed and mixed into 100 parts of water-absorbent resin particles, and heated at 80°C. Then, 0.5% of silicon dioxide (Aerosil 200, manufactured by Nippon Aerosil Co., Ltd.) was added as an inorganic powder to obtain a water-absorbent resin. The physical properties of the obtained water-absorbent resin were measured. The results are shown in Table 1.

[0153] Example 5 A monomer aqueous solution was prepared by mixing 67.0 parts of a 37% aqueous sodium acrylate solution, 10.2 parts of acrylic acid, 0.084 parts of polyethylene glycol diacrylate (average number of moles of ethylene oxide added: 9) and 22.0 parts of water. Nitrogen was blown into the aqueous monomer solution in a tray to reduce the dissolved oxygen in the solution to 0.1 ppm or less. The temperature of the aqueous monomer solution was then adjusted to 18°C ​​under a nitrogen atmosphere, and then 0.16 parts of a 5% aqueous sodium persulfate solution, 0.16 parts of a 5% aqueous 2,2'-azobis(2-amidinopropane) dihydrochloride solution, 0.15 parts of a 0.5% aqueous L-ascorbic acid solution and 0.17 parts of a 0.35% aqueous hydrogen peroxide solution were added dropwise in that order with stirring. Polymerization started immediately after the addition of hydrogen peroxide. Then, stirring was stopped, and the temperature of the monomer reached a peak temperature 10 minutes later. The peak temperature was 85°C. The tray was then immersed in a water bath at 80° C. and aged for 10 minutes, and the resulting transparent hydrogel-like crosslinked polymer was crushed with a meat chopper.

[0154] The finely divided hydrogel crosslinked polymer (particulate hydrogel) was then spread on a 50 mesh (mesh size: 300 μm) wire net and dried with hot air at 180° C. for 30 minutes to obtain a dried polymer.

[0155] The obtained dried polymer was pulverized in a pulverizer and classified into those that passed through a 500 μm sieve and remained on a 105 μm sieve, to obtain a water-absorbent resin powder.

[0156] 100 parts of the obtained water absorbent resin powder was mixed with a composition liquid consisting of 0.05 parts of ethylene glycol diglycidyl ether, 1 part of propylene glycol, 3 parts of water, and 1 part of isopropyl alcohol, and the mixture was heated at 180°C for 40 minutes to obtain a water absorbent resin. The obtained water absorbent resin was measured for each physical property. The results are shown in Table 1.

[0157] Example 6 Using the apparatus shown in Figure 3 described in US Patent Publication No. 2004 / 0092688A1, the water absorbent resin powder and the water absorbent resin were produced as follows. First, the flow rates of 48.5 wt% sodium hydroxide aqueous solution were set to 5.13 g / s, acrylic acid to 6.09 g / s, 30 wt% polyethylene glycol diacrylate (average molar number of added ethylene oxide: 9) aqueous solution (I) to 0.15 g / s, solution (II) obtained by mixing 50.0 parts by mass of 1.0 wt% 2-hydroxymethyl-2-methylpropiophenone in acrylic acid and 50.0 parts by mass of 0.54 wt% aqueous solution of trisodium diethylenetriaminepentaacetate to 50.0 parts by mass, and water to 4.63 g / s were set, and each solution was mixed using the apparatus shown in Figure 3 described in US Patent Publication No. 2004 / 0092688A1 to produce a monomer liquid.

[0158] The temperature of the prepared monomer liquid was stable at about 95°C. The monomer liquid was stirred with a stirring device in which an element with a length of 18.6 mm, a diameter of 6 mm, and a twist of 1.5 turns was inserted into a pipe with a diameter of 6 mm to form a static mixer. After stirring, a 2 wt% aqueous solution of sodium persulfate, which is a polymerization initiator, was added to the stirred monomer liquid at a flow rate of 0.511 g / s at a position about 3 cm downstream from the rear end of the element to obtain a mixed liquid. The mixed liquid was supplied to a belt polymerization apparatus having an endless belt with a length of 3.8 m and a width of 60 cm, the surface of which was coated with a fluororesin, a UV lamp was installed on the belt, the bottom and periphery were heated and kept at about 100°C, and an intake pipe for collecting evaporated water was installed in the center, and polymerization was continuously performed to obtain a band-shaped hydrogel-like crosslinked polymer. The length of the pipe from the time when the polymerization initiator was added to the monomer liquid to the discharge port (supply port) to the polymerization apparatus was 30 cm.

[0159] The obtained band-like hydrogel crosslinked polymer having a surface temperature of about 70° C. was continuously pulverized with a meat chopper to obtain a finely divided hydrogel crosslinked polymer (particulate hydrogel).

[0160] The resulting finely divided hydrogel crosslinked polymer was then dried with hot air at 180° C. to obtain a dry polymer.

[0161] The obtained dried polymer was pulverized by a roll mill, and further classified and mixed by JIS standard sieves with mesh sizes of 850 μm and 150 μm, to obtain a water absorbent resin powder having a weight average particle size of 350 μm, σζ=0.36, and a ratio of particles less than 150 μm being 2% of the total.

[0162] 100 parts by mass of the obtained water absorbent resin powder was uniformly mixed with an aqueous surface crosslinking agent solution consisting of 0.025 parts by mass of ethylene glycol diglycidyl ether, 1.5 parts by mass of 1,2-propanediol (melting point -59°C), and 3.5 parts by mass of water heated to 40°C, and the mixture was heat-treated at 100°C for 45 minutes. Thereafter, the mixture was sized using a JIS standard sieve with an opening of 850 μm to obtain water absorbent resin particles with a crosslinked surface.

[0163] Next, 100 parts by mass of the obtained water-absorbent resin particles were mixed with hydrotalcite (product name: DHT-6, manufactured by Kyowa Chemical Industry Co., Ltd., Mg 6 Al 2 (OH) 16 CO 3 4H 2 0.3 parts by weight of hydrotalcite (volume average particle diameter: 0.5 μm) was mixed. 30 g of the water-absorbent resin was placed in a 225 mL mayonnaise bottle together with the hydrotalcite, and mixed for 3 minutes by vibration with a paint shaker (manufactured by Toyo Seiki Co., Ltd.) to obtain a water-absorbent resin. The physical properties of the obtained water-absorbent resin were measured. The results are shown in Table 1. It should be noted that 95 mass % or more of the obtained water-absorbent resin was within the particle size range of 150 μm or more and less than 850 μm.

[0164] Example 7 In a polypropylene container with an inner diameter of 80 mm and a capacity of 1 liter, covered with polystyrene foam as an insulating material, 291 g of acrylic acid, 0.43 g (0.02 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (average number of moles of ethylene oxide added: 9) as an internal crosslinking agent, 1.80 g of a 1.0 mass % aqueous solution of diethylenetriamine pentacetate·pentasodium, and 3.60 g of a 1.0 mass % acrylic acid solution of IRGACURE (registered trademark) 184 were mixed to prepare a solution (A), and 247 g of a 48.5 mass % aqueous solution of sodium hydroxide and 255 g of ion-exchanged water adjusted to 50°C were mixed to prepare a solution (B). The solution (B) was quickly added to the solution (A) stirred at 800 rpm using a 5 cm long magnetic stirrer, and mixed to obtain a monomer aqueous solution (C). The temperature of the monomer aqueous solution (C) rose to about 100°C due to the heat of neutralization and heat of dissolution. The neutralization rate of the acrylic acid was 73.5 mol %.

[0165] Next, 1.8 g of a 3% by mass aqueous solution of sodium persulfate was added to the aqueous monomer solution (C), and after stirring for about 1 second, the solution was immediately poured into a stainless steel bat-shaped container with Teflon (registered trademark) attached to the inside in an open system. At the same time as pouring the aqueous monomer solution into the stainless steel bat-shaped container, ultraviolet light was irradiated.

[0166] Polymerization started soon after the monomer solution was poured into the tray (temperature at the start of polymerization was 98°C), and the polymerization reached its peak temperature within about one minute. After three minutes, the UV irradiation was stopped, and the hydrogel-like crosslinked polymer was taken out. This series of operations was carried out in a system open to the atmosphere.

[0167] The obtained hydrogel-like crosslinked polymer was pulverized using a meat chopper (MEAT-CHOPPER TYPE: 12VR-400KSOX, Iizuka Kogyo Co., Ltd., die hole diameter: 6.4 mm, number of holes: 38, die thickness: 8 mm) to obtain a finely divided hydrogel-like crosslinked polymer (particulate hydrogel) (mass average particle diameter: 1000 μm).

[0168] This finely divided hydrogel crosslinked polymer was spread on a wire net with a mesh size of 50 mesh (opening size of 300 μm) and dried with hot air at 180° C. to obtain a dried polymer.

[0169] The obtained dried polymer was pulverized by a roll mill and further classified by JIS standard sieves with meshes of 850 μm and 150 μm to obtain an irregularly pulverized water absorbent resin powder (solid content 96% by mass).

[0170] Next, the obtained water absorbent resin powder was transferred to a rotary mixer manufactured by Lödige AG in Germany, and a surface cross-linking agent aqueous solution consisting of 0.03 parts by mass of ethylene glycol diglycidyl ether, 1.0 parts by mass of propylene glycol, and 3.0 parts by mass of water was uniformly mixed with 100 parts by mass of the water absorbent resin powder, and heat-treated at 100°C for 45 minutes. Thereafter, the particles were sized using a JIS standard sieve with an opening of 850 μm to obtain water absorbent resin particles with cross-linked surfaces. The obtained water absorbent resin particles were irregular in shape, and 95% by mass or more were contained in the range of 150 μm or more and less than 850 μm.

[0171] Next, 100 parts by mass of the obtained water-absorbent resin particles were mixed with hydrotalcite (product name: DHT-6, manufactured by Kyowa Chemical Industry Co., Ltd., Mg 6 Al 2 (OH) 16 CO 3 4H 2 0.3 parts by weight of hydrotalcite (volume average particle diameter: 0.5 μm) was mixed for 3 minutes to obtain a water absorbent resin. The mixing was performed by placing 30 g of the water absorbent resin together with hydrotalcite in a 225 mL mayonnaise bottle and vibrating with a paint shaker (manufactured by Toyo Seiki Co., Ltd.). The physical properties of the obtained water absorbent resin were measured. The results are shown in Table 1. Of the obtained water absorbent resin, 98.6 mass % or more was within the particle size range of 150 μm or more and less than 850 μm.

[0172] Example 8 The physical properties were measured for the water absorbent resin powder obtained in Example 4. The results are shown in Table 1.

[0173] Example 9 The physical properties were measured for the water absorbent resin powder obtained in Example 6. The results are shown in Table 1.

[0174] Comparative Example 1 In a 2-liter polypropylene container, 421.7 g of acrylic acid, 2.4 g of polyethylene glycol diacrylate (average number of moles of ethylene oxide added: 9) as an internal crosslinking agent, 11.3 g of 1.0 wt% aqueous solution of trisodium diethylenetriaminepentaacetate, 140.4 g of 48.5 wt% aqueous solution of sodium hydroxide, 4.4 g of 1.0 wt% aqueous solution of polyoxyethylene (20) sorbitan monostearate (manufactured by Kao Corporation), and 390.3 g of deionized water (ion-exchanged water) were added and mixed to prepare an aqueous monomer solution (a'). The temperature of the aqueous monomer solution (a') rose to 62.9°C due to the heat of neutralization in the first stage immediately after preparation. Next, the aqueous monomer solution (a') was cooled while stirring. When the liquid temperature reached 38°C, 211.9 g of a 48.5 wt % aqueous sodium hydroxide solution adjusted to 40°C was added to the aqueous monomer solution (a') and mixed to prepare an aqueous monomer solution (a).

[0175] At this time, the temperature of the monomer aqueous solution (a) rose to 81.7°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5 wt% sodium hydroxide aqueous solution, a precipitate was observed, but it gradually dissolved and became a transparent homogeneous solution. Next, nitrogen gas was introduced into the monomer aqueous solution (a) at 0.1 L / min for 5 seconds using a Kinoshita glass bowl filter (filter particle No. 4 / Kinoshita Rika Kogyo Co., Ltd.). Next, 17.6 g of a 4.0 wt% sodium persulfate aqueous solution was added to the monomer aqueous solution (a) in a stirred state, and then immediately poured into a stainless steel bat-shaped container (bottom 340 x 340 mm, height 25 mm, inner surface; Teflon (registered trademark) coating) in an open-air system. The time from the start of the second neutralization to pouring the monomer aqueous solution (a) into the vat-shaped container was 55 seconds, and the vat-shaped container was heated using a hot plate (NEOHOTPLATE HI-1000 / Iuchi Seiei-do Co., Ltd.) until the surface temperature reached 40°C. The polymerization reaction started 60 seconds after the monomer aqueous solution (a) was poured into the vat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than that of the vat-shaped container. Three minutes after the start of the polymerization reaction, a hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel") was taken out. The series of operations was carried out in an open-air system. The peak temperature during polymerization was 108°C.

[0176] The hydrogel obtained by the polymerization reaction was crushed into a particulate hydrogel using a meat chopper (HL-3225N, plate hole diameter: 8.0 mm / Remacom Co., Ltd.) The hydrogel was fed at a rate of 230 g / min, and gel crushing was performed while adding deionized water adjusted to 90°C at a rate of 50 g / min in parallel with the feeding of the hydrogel.

[0177] The resulting particulate hydrogel was spread on a stainless steel wire mesh with 850 μm mesh and dried by passing hot air through it at 180° C. for 30 minutes to obtain a dried polymer. Subsequently, the dried polymer obtained by the drying operation was pulverized using a roll mill (WL type roll pulverizer / Inoguchi Giken Co., Ltd.), and then classified using JIS standard sieves with openings of 710 μm and 45 μm. By the series of operations, an irregularly pulverized water absorbent resin powder was obtained. A surface crosslinking agent solution consisting of 0.3 parts by weight of ethylene carbonate, 0.6 parts by weight of propylene glycol, 3.0 parts by weight of deionized water (ion-exchanged water), and 0.001 parts by weight of polyoxyethylene (20) sorbitan monostearate (Kao Corporation) (10 ppm relative to the water absorbent resin powder) was added to 100 parts by weight of the obtained water absorbent resin powder and mixed uniformly. Thereafter, the mixture was heat-treated at 208°C for 40 minutes to perform surface crosslinking.

[0178] After the heat treatment, the obtained water-absorbent resin particles were crushed until they passed through a JIS standard sieve with an opening of 850 μm, to obtain a comparative water-absorbent resin. The obtained comparative water-absorbent resin was measured for each physical property. The results are shown in Table 1.

[0179] [Table 1]

[0180] 〔summary〕 By comparing Examples 1 to 9 with Comparative Examples, it is found that the water-absorbent resins having a 20-hour filtration rate of 60% or less have excellent handleability after swelling with pure water. In addition, it is found from Examples 1 to 3 and 6 to 9 that the water-absorbent resins having a lower 20-hour filtration rate have good handleability even when swollen at a lower rate of about 67 to 75 times. That is, it is found that the handleability is good over a wide range of swelling rates, and that in industrial applications, particularly in applications as fixing agents for hydrated loose materials, bedding materials, waste liquid solidification, etc., the range of the amount of water-absorbent resin added to obtain the effect of the present application (improved handleability after absorbing liquid) is wide, and mixing work after absorbing liquid may become unnecessary, making it a suitable water-absorbent resin with fewer restrictions on use. Among them, the water-absorbent resins of Examples 1 to 2 and 6 to 9 having a low 10-minute filtration rate have excellent handleability when swollen at an even lower rate of 50 times or less, and are more suitable for the above-mentioned applications than Example 3.

[0181] In addition, looking at the examples of the present application, it appears that a water-absorbent resin with a higher CRC has excellent handling properties after swelling over a wide range of magnifications, but as can be seen from Examples 3 and 4, a fine particle size (D50) also affects the handling properties after swelling. In addition, as can be seen from Examples 4 and 7, in which the CRC of the water-absorbent resin is at the same level, differences in the conditions of the heat treatment process in the manufacturing process of the water-absorbent resin also affect the handling properties after swelling. That is, it is understood that the handling properties of the actual water-absorbent resin after swelling are expressed by intertwining complex factors including the CRC, mass average particle size (D50), manufacturing method, etc. Therefore, it is understood that the handling properties of the water-absorbent resin after swelling cannot be unambiguously defined by conventional parameters such as CRC and mass average particle size (D50). On the other hand, it is understood that the 20-hour filtration rate (and 10-minute filtration rate) specified in this specification can be used to evaluate the handling properties of the water-absorbent resin by taking into account the effects of these complex factors. [Industrial Applicability]

[0182] INDUSTRIAL APPLICABILITY The water-absorbent resin according to one embodiment of the present invention can be suitably used for industrial applications, in particular as a fixing agent for wet bulk matter, bedding material, solidification of waste liquid, and the like.< / crc> < / crc>

Claims

1. A polyacrylic acid (salt)-based water-absorbing resin, After swelling in pure water for 20 hours, the filtration rate is 60% or less. A water-absorbent resin for use as a fixative, which has a filtration rate of 50% or less after swelling in pure water for 10 minutes.

2. 2. The water-absorbent resin for a fixing agent according to claim 1, which has a filtration rate of 45% or less after swelling in pure water for 20 hours.

3. The water-absorbing resin for a fixing agent according to claim 1 or 2, which has a CRC of 35 g / g or more.

4. The water-absorbing resin for a fixing agent according to any one of claims 1 to 3, having a CRC of 38 g / g or more.

5. The water-absorbent resin for a fixing agent according to any one of claims 1 to 4, having a mass median particle diameter (D50) of 200 to 800 µm.

6. A fixing agent comprising the water-absorbent resin for fixing agents according to any one of claims 1 to 5.

7. The fixative according to claim 6, which is a fixative for moist bulk material.

8. A method for modifying moist rose product, comprising a step of contacting the fixing agent according to claim 6 or 7 with moist rose product.

9. A method for producing modified hydrated rose product, comprising a step of contacting the fixing agent according to claim 6 or 7 with hydrated rose product.

10. The fixing agent according to claim 6, which is a fixing agent for bedding.

Citation Information

Patent Citations

  • Production of highly water-absorptive polymer

    JP1986211305A

  • Production of polymer having high water-absorptivity

    JP1986213206A

  • Excretion treating material of barn

    JP1987044126A

  • Fiber sheet and method for producing the same

    JP2019035156A

  • Method for preventing adhesion and clogging of mineral raw materials

    JP6825738B1